Enhancement of adhesive bonding strength: surface roughness and wettability characterisations / Norazwani Muhammad Zain, Sahrim Hj Ahmad and Ernie Suzana Ali - Muhammad Zain, Norazwani; Hj Ahmad, Sahrim; Ali, Ernie Suzana (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2014)
In order to enhance the adhesive bonding, two different methods of surface treatments have been carried out on aluminum alloy 2024-T3 substrate i.e. alkaline etching and silane treatment. The topology and surface chemical analyses of treated alloy were investigated by AFM and XPS, respectively. The effect of surface treatments on the wettability and adhesive bonding strength were also studied. Three different formulations of polyurethane adhesive by varying the NCO: OH ratio that were prepared from the reaction of green polycaprolactone (PCL) polyol and diisocyanate. Silane treatment showed better wettability and adhesive bonding strength compared to alkaline etching surface treatment.